Performance Study of Single-Phase Self-Excited Induction Generator in Stand-Alone System - Ikhsan, Muhammad (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The performance of Self-Excited Induction Generators is significantly influenced by excitation conditions and load variations. One of the critical factors in maintaining voltage and frequency stability is the selection of an appropriate shunt capacitor to supply the required reactive power. This study investigates the impact of shunt capacitance variation on Self-Excited Induction Generators performance under different operating conditions. Experimental analysis is conducted to examine the relationship between shunt capacitance, terminal voltage, excitation current, and frequency stability at various load levels. The results demonstrate that increasing shunt capacitance enhances terminal voltage and excitation current. Furthermore, this study presents best practices for determining the excitation capacitance to ensure stable SEIG voltage generation in standalone power generation applications.